Antilipoperoxidative and anti-inflammatory efficacy of multifunctional sunscreens containing ferulic acid - Silva, Rafael Sauce (2020)
Unprotected chronic exposure to ultraviolet radiation generates many harmful effects to human skin and UV filters are essential to health, however, traditional sunscreens do not provide enough protection against cutaneous oxidative stress, a process amplified by UV radiation. Therefore, is been proposed the development of multifunctional photoprotective formulations, acting in the absorption/reflection of UV radiation and assisting in cutaneous homeostasis. In the present study, ferulic acid is used in conjunction with two sunscreens, bemotrizinol and ethylhexyl triazone, for the determination of biosafety and efficacy methods, using techniques that better elucidate the effects of ferulic acid. Skin permeation assays were performed by applying a formulation containing the three substances in the stratum corneum of volunteers, which were removed by the tape stripping method (ex vivo) with follow quantification by high performance liquid chromatography (HPLC). The test was able to evaluate the penetration depth of the substances, characterizing them. In addition, the simultaneous quantification of the three substances was performed by a single and fast method, facilitating their analysis and improving the technique. Also, TBARS (thiobarbituric acid reactive substances) assays were performed in stratum corneum removed by tape stripping (ex vivo), evaluating the potential of cutaneous lipid peroxidation, with or without ferulic acid. To date, it is the first time that TBARS method is used to characterize the stratum corneum (ex vivo) and quantified by HPLC. The protocol developed may aid in the efficacy of antioxidant agents in studies aimed at elucidating the level of lipid peroxidation caused by drugs and cosmetics, and even in carrying out baseline studies characterizing different ethnicities and genders. As last, an anti-inflammatory in vivo assay with Laser Doppler flowmetry equipment was used to compare the sunscreen formulation with or without ferulic acid. Data indicated that the antioxidant reduced the angular coefficient of the perfusion units, mitigating the inflammatory effects. Furthermore, a significant difference was found between the genders, suggesting a more pronounced inflammatory reaction in women. Ferulic acid proved to be a valuable resource, besides being safe and raise the SPF of sunscreens, it also mitigates the effects of inflammation.